Жінки в іт-сфері: можливості і перспективи - Мірошниченко, P. O.; Шостак, М. В. (ХНУРЕ, 2019)
The work considers the problem of possible professional realization of women in IT-sphere in the conditions of formation and development of the information society. The thought of the necessity of overcoming gender stereotypes and gender stratification in Ukrainian society in justified.